Penile-sparing modalities in the management of low-stage penile cancer - Paurush Babbar; Nitin Yerram; Alice Crane; Daniel Sun; Kyle Ericson; Andrew Sun; Abhinav Khanna; Hadley Wood; Andrew Stephenson; Kenneth Angermeier (Urology Annals, 2018)
Penile-sparing modalities are gaining widespread adoption for the management of low-stage penile cancer due to an increasing demonstration of sound oncologic, cosmetic, sexual, psychosocial, and quality of life outcomes. This review aims to provide a comprehensive overview of the respective treatment options in the armamentarium of the practicing urologist in dealing with this rare but problematic condition.